Integrasi Pembelajaran Produktif untuk Membangun Karakter dan Jiwa Kewirausahaan di SMK - Arif Susanto; Agung Setiawan; Karjiono Karjiono; Beni Nugroho; Satria Pradana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Productive program learning in Vocational High Schools has an important role in developing student competencies, both in technical aspects and in entrepreneurial skills. This study aims to identify an effective learning model for productive programs in Vocational High Schools, which includes teaching materials, learning methods, and evaluation of learning outcomes, with a focus on developing entrepreneurial character among graduates. The method used in this study is Research and Development (R&D) by following the development procedure proposed by Borg and Gall. Data analysis was carried out descriptively, by describing the validity, practicality, and effectiveness of product-based learning models in the fields of technology and engineering, tourism, and business and management. The application of the research and development approach in the fields of technology and engineering, tourism, and business and management allows the development of a learning model for productive programs in SMK that prioritizes three important components. First, learning materials are directed at productive activities such as making goods and services, with an emphasis on developing entrepreneurial character. Second, the learning method uses a task based or project based strategy that encourages active student involvement. Third, evaluation of learning outcomes is carried out through performance assessment techniques that assess not only the final product but also the learning process that is gone through. This kind of learning model is expected to equip students with practical skills and entrepreneurial abilities to support their readiness to face the world of work.